Chrysura izadiae sp. nov., a new cuckoo wasp (Hymenoptera, Chrysididae) from Southern Iran - Strumia, Franco; Fallahzadeh, Majid; Izadi, Elaheh (Zootaxa, 2016)
Chrysura Dahlbom, 1845 is the second largest genus in the Chrysidini tribe. It is essentially a Holarctic genus composed of over 100 species. The largest diversity is observed in the western Palaearctic Region. Important diagnostic features are the relatively flat and finely punctured face, absence of transverse frontal carina, the edentate metasomal tergum 3, and male flagellomeres 2–5 (especially 2–4) bulging ventrally (Kimsey & Bohart 1991). Kimsey & Bohart (1991) divided Chrysura into five species-groups: candens, cuprea, dichroa, austriaca and radians. Recently, Rosa and Lotfalizadeh (2013) proposed Ch. baiocchii as a new species-group. Within the Ch. dichroa species-group, including about 20 species, the largest richness is observed in the Mediterranean Region where a number of sibling species are present, making taxonomy of this group particularly difficult (Linsenmaier 1959, Arens 2001, 2002). The male genitalia have an important taxonomic value for species identification. The body colour pattern is rather constant in each species-group. All known species in the Ch. dichroa species-group have “head blue to green on vertex at least”, “pronotal dorsum all or nearly all coppery-red; scutum and scutellum mostly red”, “metanotum, propodeum, and pleuron mostly or all purple to green” (Kimsey & Bohart 1991). According to Linsenmaier (1959) the Ch. dichroa species-group has the above body colour with in addition tegula non coppery-red. Up to now, the following seven species belonging to the Ch. dichroa species-group are known in Iran (Rosa et al. 2013, Rosa & Lotfalizadeh 2013, Strumia & Fallahzadeh 2015): Chrysura filiformis (Mocsáry, 1889); Ch. laconiae (Arens, 2001); Ch. laevigata (Abeille de Perrin, 1879); Ch. lydiae (Mocsáry, 1889); Ch. psudodichroa (Linsenmaier, 1959); Ch. purpureifrons (Abeille de Perrin, 1878); Ch. simuldichroa (Linsenmaier, 1969).